2006
DOI: 10.1530/rep.1.00852
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the coeliac ganglion in the luteotrophic effect of androstenedione in late pregnant rats

Abstract: Using the ex vivo coeliac ganglion-superior ovarian nerve-ovary system at the end of pregnancy when luteal regression starts, we investigated whether, when administered systemically or when added directly to the ganglion compartment, androstenedione (A 2 ) can reverse such regression, and whether the neural (noradrenaline (NA)) and endocrine (A 2 ) joint action modifies the release of ovarian progesterone. The experimental groups were as follows: group 1 -A 2 injected systemically 48 h before incubation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…The luteotropic effect of androstenedione has been widely demonstrated in different experimental schemes (Carrizo et al 1994, Hillier et al 1994, Thordarson et al 1997, Goyeneche et al 2002 and even in the celiac ganglion-SON-ovary via SON (Casais et al 2006). Our results indicate that the ganglionic cholinergic action, mainly on the liberation of androstenedione, would act favoring the luteal regression occurring at the end of gestation which is necessary for the delivery to occur.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…The luteotropic effect of androstenedione has been widely demonstrated in different experimental schemes (Carrizo et al 1994, Hillier et al 1994, Thordarson et al 1997, Goyeneche et al 2002 and even in the celiac ganglion-SON-ovary via SON (Casais et al 2006). Our results indicate that the ganglionic cholinergic action, mainly on the liberation of androstenedione, would act favoring the luteal regression occurring at the end of gestation which is necessary for the delivery to occur.…”
Section: Discussionmentioning
confidence: 50%
“…Their synthesis is regulated by the hypophysial gonadotropins and modulated by placental factors (Rothchild 1981) among others (Villavicencio et al 2002) and the neural effect mainly caused by the superior ovarian nerve (SON) (Lawrence & Burden 1980, D'Albora et al 2000, Aguado 2002. Using different experimental schemes, we have demonstrated that the SON modifies the liberation of ovarian steroids in different stages of life in rats (De Bortoli et al 2000, Sosa et al 2000, Casais et al 2001, 2006, Forneris & Aguado 2002. Fibers from the SON directly innervate the theca and secondary interstitial cells and they exert an indirect action on the corpus luteum (Erickson et al 1985).…”
Section: Introductionmentioning
confidence: 88%
“…We have shown that under our experimental ex vivo conditions the SON releases catecholamines and nitric oxide to the ovarian compartment [6,14,16]. It has been shown that the CG expresses the enzyme tyrosine hydroxylase that controls the synthesis of norepinephrine [30].…”
Section: Discussionmentioning
confidence: 74%
“…We have provided evidence that systemic administration of androstenedione or its addition to the ganglion compartment of the CG-SON-ovary system, opposes to the functional regression of the corpora lutea at the end of pregnancy in rats [14][15][16]. We further demonstrated that androgen receptor immunoreactive proteins are present in the neurons of the CG before parturition, suggesting that the indirect luteotropic activity of androstenedione may be mediated by these receptors and that they can eventually modulate the synthesis of neurotransmitters by the SON [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation